Treatment results of adult patients with primary bone tumours of the humerus with the use of the oncological modular endoprosthesis - Goryń, Tomasz; Pieńkowski, Andrzej; Komor, Andrzej; Dziewirski, Wirginiusz; Zdzienicki, Marcin; Kozioł, Maria; Rutkowski, Piotr (Contemporary Oncology/Współczesna Onkologia, 2017)
Aim of the study : Primary bone tumours are relatively rare, but their diagnosis and treatment is difficult and connected with a high risk of complications. The goal of this report is a retrospective evaluation of outcomes in patients with primary tumours of the humerus treated in our centre with the use of modular endoprosthetic reconstruction. Material and methods : Currently, surgical treatment is a standard procedure for local therapy, with wide tumour-free margin resection after a planned multidisciplinary and individualised strategy of tumour management based on the diagnostic biopsy result. The best option for patients to avoid disability is simultaneous surgical reconstruction aiming to spare the limb and its functionality. Results : In this report, we present the results of treatment of our 11 adult patients suffering from primary bone tumours of the humerus, who have undergone wide bone resection followed by reconstruction with the use of a modular MUTARS® endoprosthesis. Conclusions : The study showed that prosthetic reconstruction of the resected humerus due to a primary bone tumour is safe and acceptable for patients; despite the fact that limitation of active abduction of the shoulder is up to 20 grades, this surgical procedure provides satisfactory limb function.